2013
DOI: 10.1002/jsfa.6071
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and instrumental texture measurements for assessing grape seed parameters during fruit development

Abstract: This research showed that both seed sensory attributes and instrumental texture properties are indicators of grape ripening. However, these properties could be affected by the harvest season and growing location. As no clear correlation was found between the seed sensory attributes and instrumental texture parameters, a revision of the sensory method available in the literature could be suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…A work recently published also highlighted that the seed texture properties measured by compression testing are positively correlated with each other (Letaief et al, 2013). The differentiating power of F s is shown in Fig.…”
Section: Grape Variety Colourmentioning
confidence: 73%
See 2 more Smart Citations
“…A work recently published also highlighted that the seed texture properties measured by compression testing are positively correlated with each other (Letaief et al, 2013). The differentiating power of F s is shown in Fig.…”
Section: Grape Variety Colourmentioning
confidence: 73%
“…Nevertheless, the changes occurred only in seed stiffness (E s ) for sorted Cabernet Sauvignon grapes sampled at different harvest dates, even if one density class per sampling date was selected to emphasise the physiological differences among grape ripening stages (Rolle et al, 2012a). Some researchers also noted that most of the texture parameters of the seeds became steady three weeks after the end of véraison (Letaief et al, 2013). During the on-vine dehydration process of Mondeuse grapes, stability in the values of seed mechanical properties was reached after the 75 th withering day .…”
Section: Grape Variety Colourmentioning
confidence: 99%
See 1 more Smart Citation
“…Texture analysers measure the physical nature of a sample, converting mechanical properties into several physical parameters, such as firmness, chewiness, brittleness, adhesiveness, elasticity and extensibility. Texture analysers are widely used for the analysis of the firmness of grape skin and seeds (Letaief et al , , Maury et al , Zsófi et al ). Models used include texture profile analysis (TPA), cut, tension, bend fracture and puncture tests.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 10 years, other subjective methods have been developed to determine phenolic maturity. These experiments are based on the knowledge of oenologists and their ability to taste berries and seeds (Letaief et al, 2013). In 2005, Ristic and Iland (2005) initiated research addressing seed development and tannin accumulation and showed correlations with colour evolution.…”
Section: Introductionmentioning
confidence: 99%